Empirical Factors Influencing Food Security in Nigeria. Do Local Farmer Investors In Farming Activities Mitigate Food Shortages? Evidence in the Short and Long Run. - Nnaemeka, Nathaniel Obasi (American Journal of Agriculture, 2022)
Purpose: What are the significant factors influencing food security in Nigeria? What is the food security status of rural farmers? Do local farmer investors positively influence agricultural output productivity and mitigate food shortages in the long run and short run? What is the alternative source of mitigating food shortages? Through these questions, the objective of this research was to identify factors that affect food security as well as identifying empirical sources of improving food security and putting good policies in place to actualise it. Methodology: The study has a research design covering a sample size of 145 farmers using a structured questionnaire with random sampling technique to investigate the empirical factors influencing food security in Nigeria and method of data analysis used was logistic regression analysis. Time series data from Central Bank of Nigeria Statistical Bulletin (2019) was used to investigate the role of local farmer investors in agricultural productivity/mitigation of food shortages using Johansen co-integration (long run) and Granger causality (short run) techniques. Findings: The logistic regression result computed from the survey data from the respondent farmers revealed that age, total cost of production, farm income and health expenditure are significant factors that influence food security. Result further showed that food security status of rural farmers is not secured. Through the short run and long run investigation, the empirical results covering the period of 1980-2018 in Nigeria revealed that local farmer investors positively influence agricultural productivity and mitigate food shortages by 2.99 percent. The findings further revealed that foreign farmer investors contribute to agricultural output productivity and mitigate food shortages by 4.90 percent, thus an alternative source of mitigating food shortages in Nigeria. Unique contribution to practice and policy: Its unique contribution to practice and policy is that policy makers will shift in line with the findings. Policy makers should ensure that policies that encourage local farmer investors as well as foreign farmer investors are put in place and adhered to help mitigate food shortages in Nigeria.